School participation, supports and barriers of students with and without disabilities. Issue 4 (13th June 2013) - Coster, W.; Law, M.; Bedell, G.; Liljenquist, K.; Kao, Y.‐C.; Khetani, M.; Teplicky, R.
Abstract Background We compared school participation patterns of students ages 5–17 with and without disabilities and examined whether features of the school environment were perceived to help or hinder their participation. Methods Parents (n = 576) residing in the USA and Canada completed the Participation and Environment Measure for Children and Youth (PEM‐CY) via the internet. Results Parents of students with disabilities reported that their children participated less frequently in school clubs and organizations and getting together with peers outside the classroom and that they were less involved in all school activities. Parents of students with disabilities also were significantly more likely to report that features of the environment hindered school participation and that resources needed to support their child's participation were not adequate. Conclusions Parents of students with disabilities report that their children are participating less in important school‐related activities. Barriers limiting school participation include features of the physical and social environment as well as limited resources.